The targeting imaging and treatment capacity of gelsolin-targeted and paclitaxel-loaded PLGA nanoparticles in vitro and in vivo - Ji, Jiamei; Qin, Haocheng; Yang, Yan; Wu, Jun; Wu, Juan (Frontiers in Bioengineering and Biotechnology, 2022)
As a vital sign of carcinomas, lymph node metastasis is closely related to poor prognosis due to lack of identification and effective treatment in the early stage. Nanoscale contrast agents targeting specific tumor antigens are expected to identify tumor metastasis in the early stage and achieve precise treatment. As a biomarker in the early stage of tumor invasion and metastasis, gelsolin (GSN) might be a promising molecular target to identify and screen tumor metastasis through the lymphatic system. Therefore, GSN-targeted paclitaxel-loaded poly (lactic-co-glycolic acid) nanoparticles (GSN-PTX-PLGA NPs) were prepared and their physicochemical properties, encapsulation efficiency, drug loading and dissolution were determined. Besides, uptake experiments and fluorescent imaging system were used to evaluate their targeting capability. The targeting imaging and treatment capacity were also assessed by experiments in vitro and in vivo. The diameter of the GSN-PTX-PLGA NPs was 328.59±3.82 nm. Hca-F cells with GSN-PLGA NPs showed stronger green fluorescence than Hca-P cells. DiI-labeled GSN-PLGA NPs in tumor-bearing mice and isolated organs exhibited more prominent fluorescence aggregation. The imaging of GSN-PLGA NPs was satisfactory in vitro, and the echo intensity gradually increased with increasing concentrations of GSN-PLGA NPs. After treatment with GSN-PTX-PLGA NPs, there was an obvious decrease in tumor volume and lymph node metastasis rate compared to the other groups (P<0.05). In conclusion, GSN-PTX-PLGA NPs have a remarkable targeting capacity in vivo and in vitro and they effectively inhibit tumor growth and lymph node metastasis in vivo.